Current‐sharing bus and fuzzy gain scheduling of proportional–integral controller to control a parallel‐connected AC/DC converter. Issue 10 (1st October 2014) - Kanthaphayao, Yutthana; Chunkag, Viboon
Abstract : In this study, a current‐sharing bus and fuzzy gain scheduling of proportional–integral (PI) controller to control a parallel‐connected AC/DC converter are proposed. A simple current‐sharing circuit is applied to divide the load current to calculate the peak input current of each converter module. Fuzzy gain scheduling of PI controller is used to compensate for the error of the output voltage. The dsPIC30F6010 microcontroller is applied in the voltage loop control. In addition, a hysteresis control circuit is used to control the current loop. The experimental performance evaluation is conducted on a prototype, with three converter modules that are parallel‐connected, has 250 W/module and has a −48 V DC output voltage. The system offers the following advantages: the tight output voltage regulates both the steady‐state operation and the transient response. The current sharing is quite good, and it is simpler to operate in the redundant mode.